Structure orientation of hemin self-assembly layer determining the direct electron transfer reaction. Issue 4 (24th November 2014) - Wang, Gui-Xia; Zhou, Yue; Wang, Min; Bao, Wen-Jing; Wang, Kang; Xia, Xing-Hua
Abstract : A strategy was proposed to control the hemin orientation via experimental models, which shows heme plane orientation dependent direct electron transfer and electrocatalysis. Abstract : We propose a strategy to control directly the orientation of hemin plane via experimental models, Hemin–His model and Hemin–MHN model with ODT. Electrochemical results show that electron communication is largely enhanced when the hemin plane is near to parallel to the electrode surface by histidine ligation in Hemin–His model, while the electron transport of hemin in Hemin–MHN model with ODT becomes relatively difficult.